2020
DOI: 10.2478/mgr-2020-0005
|View full text |Cite
|
Sign up to set email alerts
|

Scientific citizens, smartphones and social media – reshaping the socio-spatial networks of participation: Insects, soil and food

Abstract: The conjunction of citizen science and social media through the mediation of the smartphone is investigated in this Scientific Communication, following on from the last issue of the Moravian Geographical Reports (2019, Vol. 27, No. 4). Through a reconsideration of three previously published articles, in part written by the author, this paper reflects on these topics with regard to farmer innovation, local food networks and citizen-informed ecology. Each of these papers has used Twitter to gather data about pra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Mutual communication between AD operators and the local population at each stage of planning of the AD project is a crucial part of conflict free operation of such facility [46]. Generally, support for eco-innovations (as for example AD plants) is highly dependent on socio-demographic variables of population of hosting communities [47] and vary in different socio-cultural conditions [ [48], [61]]. As Florkowski et al [49] found in their study that support among population for waste to energy processing in local AD is closely linked to their education, gender, age, household size, and employment status.…”
Section: Discussionmentioning
confidence: 99%
“…Mutual communication between AD operators and the local population at each stage of planning of the AD project is a crucial part of conflict free operation of such facility [46]. Generally, support for eco-innovations (as for example AD plants) is highly dependent on socio-demographic variables of population of hosting communities [47] and vary in different socio-cultural conditions [ [48], [61]]. As Florkowski et al [49] found in their study that support among population for waste to energy processing in local AD is closely linked to their education, gender, age, household size, and employment status.…”
Section: Discussionmentioning
confidence: 99%
“…The fact that public and social media play an important role in shaping the consciousness of urban and rural residents carries both opportunities and threats. The positives include the possibility of a wide range of information distribution, both through traditional (TV) and modern (Internet and social media) channels, pluralism of content, as well as co-creation of people's attitudes, choices and behaviours (Reed, 2020). Nevertheless, it should also be kept in mind that the media can determine in a very malleable and effective, even 'programmed' way, how views, opinions, observations and regularities are formed in many areas of life (Goban-Klas, 2005).…”
Section: Turning Points and Gordian Knots Of Polish Transformationmentioning
confidence: 99%
“…The media themselves, such as the press, television, or the Internet, are the result, or product of human creativity and are guided by the dominant informational function while maintaining Jakobson’s communication scheme, including the sender and recipient of the transmitted information (Drożdż, 2014 ). We also know very well that apart from the informational and communicational functions, the media have an overwhelming influence on society, co-create people’s attitudes, choices, and behaviour (Reed, 2020 ). The media decide in a very plastic and effective, or even in a “programmed” way, about how they shape views, opinions, observations, and regularities in many areas of life (Goban-Klas, 2005 ; Ryan, 2001 ).…”
Section: Introductionmentioning
confidence: 99%